Assessment of occupational exposure to mycotoxins: relevance of biomonitoring tools - Viegas, Carla (2019)
As an alternative or as a complement to air monitoring, biomonitoring is another way of assessing exposure to mycotoxins. Biomonitoring can include the detection, in easily accessible body fluids such as blood and urine, of the parent compound (mycotoxin) and its metabolites. However, the use of biomonitoring implies the availability of information related with each mycotoxin toxicokinetics, metabolism, and bioavailability to be able to interpret correctly the results. Moreover, it is important to note that data on background dietary exposure to mycotoxins is needed to determine the additional burden of respiratory and dermal exposure in the workplace. If this background data are unavailable, a control group of individuals from the general population should be included to exclude the possibility of exposure by diet. Additionally, we should consider that the most common exposure scenario in the workplaces is exposure to mycotoxins mixtures. It is, therefore, extremely relevant, from an occupational health point of view, to be able to measure several mycotoxins in one sample. Contextual information about the workplace and tasks developed is also very relevant to obtained since levels of exposure can vary greatly between different tasks within the same industry, and characterizing exposure implies recognize which tasks implicate higher exposure. Only with this information is possible to perform a more accurate exposure and risk assessment and, consequently, identify the most suitable risk management measures to apply. Several data will be presented from past and on-going research projects to demonstrate how biomonitoring was useful and contributes to recognize which occupational settings adds significantly to the exposure resulting from the ingestion of mycotoxin-contaminated food. The different variables that promote exposure to mycotoxins in different settings will also be discussed.